Activation of cement hydration with carbon dioxide. Issue 3 (4th May 2018) - Monkman, Sean; Kenward, Paul A.; Dipple, Greg; MacDonald, Mark; Raudsepp, Mati
Abstract : Additions of carbon dioxide to hydrating concrete have been observed to result in performance benefits. In this study, oil-well cement (selected for its very low initial carbonate content) was hydrated in the presence and absence of pure CO2 gas. The evolution of the products and reactants was assessed through isothermal calorimetry, Quantitative X-ray Diffraction (QXRD), Loss on Ignition, and Total Inorganic Carbon. A one minute exposure to carbon dioxide gas during mixing improved the heat of hydration though 24 h by 8%. The amount of C-S-H formed increased by 20%, and the estimated degree of hydration increased by 23%. The carbon dioxide promoted the formation of calcium carbonate that was observed in the sample immediately after treatment with carbon dioxide. The carbonate was initially amorphous calcium carbonate not detectable with QXRD, but it changed over 24 h to crystalline calcite (CaCO3 ) detectable by QXRD.